Pengaruh Pemberian Jus Campuran Belimbing (Averhoa Carambola Linn) Dan Mentimun (Cucumis Sativus Linn) Terhadap Tekanan Darah Pasien Hipertensi Rawat Jalan Di Rumah Sakit Umum Daerah Kota Mataram - Devi Rahma; Suhaema Suhaema; Fifi Luthfiyah; Made Darawati (Poltekkes Kemenkes Mataram, 2018)
Background. Hypertension can be a risk factor for stroke, coronary heart disease, heart failure and kidney failure and is known as the thesilent killer. The prevalence of hypertension in West Nusa Tenggara Province is 24.3% (Riskesdas, 2013). Medical Record Data of Mataram City Public Hospital, hypertension became the first of the top 10 outpatient diseases in 2015. The only treatment for non-pharmacological hypertension was by increasing fruit and vegetable consumption due to high potassium content. Research Methods. The type of this research is experimentation with Randomized Control Trial (RCT) design with Pretest-Posttest with Control Group design. The number of subjects is 20 people obtained from the formula Lemeshow (1997). Both groups continued to take antihypertensive drugs, but the treatment group was given 250 ml of starfruit juice and cucumber juice for 7 days. The statistical analysis used was the paired t-test and independent t-test. Research Result. The average blood pressure before the study in the treatment group was 150/91 mmHg, in the control group it was 142/83 mmHg. The average blood pressure after the study for the treatment group was 132/81 mmHg, while the control group was 144/81 mmHg. There was a decrease in blood pressure in the treatment group after the intervention was 18 mmHg for systolic (p = 0.000) and 10 mmHg for diastolic (p = 0.004), but there was no decrease in blood pressure both systolic and diastolic in the control group. Conclusion. Giving a mixture of star fruit and cucumber juice affects the decrease in systolic and diastolic blood pressure.